Effect of several insecticides to control the lesser cornstalk borer, on maize - Cruz, Ivan; Oliveira, Lenita J.; Santos, Jamilton P. (Pesquisa Agropecuaria Brasileira, 2014)
Three field experiments were conducted including several insecticides with different formulations, dosages and application methods to control the lesser cornstalk borer (Elasmopalpus lignosellus) on maize (Zea mays L.). In relation to the application methods, insecticides were applied in furrow at planting time as seed coating and as spray after plant emergence. Evaluations were based on the number of emerged plants (initial stand), number of surviving plants (final stand), number of attacked plants, and yield. The number of attacked plants was surveyed in alternated days. Insecticides applied as planting time gave good protection of the seed and/or seedlings against soil pests. Aldrin in seed coating and endrin in furrow were among the best insecticides in relation to the number of emerged plants. However, they did not have any effect on the lesser cornstalk borer. For this insect the best insecticides were thiodicarb (035, 1 and 2.25 liters of active ingredient per 100kg of seeds), carbofuran in seed coating and granular application and methomyl in granular application. Plots treated with thiodicarb and carbofuran yielded 60% more than the untreated ones. The insecticides in spray application were not efficient in controlling the pest on maize.